Ultra-fast and effective ultrasonic synthesis of potassium borate: Santite - Ila, Sibel; Kipcak, Azmi Seyhun; Derun, Emek Moroydor (DE GRUYTER POLAND SP Z O O, 2022)
In this study, a potassium borate compound of santite is synthesized at 60 degrees C, 70 degrees C, 80 degrees C, and 90 degrees C reaction temperature for 2.5, 5, 10, and 15 min reaction time by using eight different raw material combinations of K2CO3, KNO3, NaOH, H3BO3, B2O3, Na2B4O9 center dot 5H(2)O, and Na2B4O9 center dot 10H(2)O. According to the X-ray diffraction analysis synthesized potassium borate compound is identified as santite (KB5O8 center dot 4H(2)O) with powder diffraction file no. 01-072-1688. Raman spectroscopy results showed that the synthesized compound consists of typical boron mineral bands, and the spectra obtained were in mutual agreement with potassium borate, according to the literature. Scanning electron microscopic morphologies showed that obtained santite has different particle shapes as the raw material combination changed and the particle sizes are found between 305 nm and 2.03 mu m. Overall reaction yields are found between 76.11% and 99.26%, even such lower reaction times with respect to the literature.
Keywords: particle size; potassium borate; reaction yield; santite; ultrasonic synthesis; CRYSTAL-STRUCTURE; SONOCHEMISTRY; DEHYDRATION; PRECURSOR; BORON; OXIDE; Chemistry